Extraction and antibacterial activity of Alpinia conchigera rhizome extract and 1’S -1’-acetoxychavicol acetate (ACA) against Streptococcus pneumoniae - Nor Syazwani Muhammad Zahidan,; Nur Umairah Atiqah Sabri,; Siti Noor Adnalizawati Adnan,; Khalijah Awang,; Normaliza Ab Malik, (Penerbit Universiti Kebangsaan Malaysia, 2025)
The study aimed to investigate the antibacterial effects of Alpinia conchigera rhizome extract and 1’S-1’-acetoxychavicol acetate (ACA) against Streptococcus pneumoniae strain successfully isolated from oral rinse of older adults from an old folks’ home. The grounded rhizomes of A. conchigera were macerated in hexane solvent to yield crude hexane extract. Then, A. conchigera rhizome extract was subjected to column chromatography to isolate ACA. Both A. conchigera rhizome extract and ACA were screened for the antibacterial activity against S. pneumoniae ATCC 49619 and S. pneumoniae isolate by disc diffusion test, minimum inhibitory concentration (MIC), minimum bactericidal concentration (MBC) and time kill assay. The highest inhibition zone recorded by A. conchigera rhizome extract (100 mg/mL) and ACA (100 mg/mL) were 36.83 ± 0.85 mm and 30.67 ± 0.94 mm, respectively against S. pneumoniae isolate. The MIC and MBC values recorded for A. conchigera rhizome extract and ACA against both S. pneumoniae ATCC 49619 and S. pneumoniae isolate ranging from 12.50 mg/mL to 50.00 mg/mL. Based on the time kill curve, both extracts with the concentration of 2 × MIC showed killing properties against S. pneumoniae isolate. Besides that, the morphology of S. pneumoniae isolate treated with ACA (12.50 mg/mL) was observed under scanning electron microscope and showed structural changes such as cell wall disruption and morphological disorder. Moreover, several virulence genes of S. pneumoniae were studied using RT-qPCR. It is observed that two genes, pavA and psaA function in adherence and attachment of S. pneumoniae to the host cells were downregulated while nanA which that responsible for biofilm production was upregulated. Therefore, both A. conchigera rhizome extract and ACA showed great potential as alternative antibacterial agent against S. pneumoniae.